The action of pseudo-differential operators on functions harmonic outside a smooth hyper-surface - Boutet de Monvel, Louis; Colin de Verdière, Yves (Comptes Rendus. Mathématique)
The goal of this note is to describe the action of pseudo-differential operators on the space of square integrable functions which are harmonic outside a smooth closed hyper-surface of a compact Riemannian manifold.